Peran Suami dalam Pemeliharaan Status Gizi Ibu Hamil di Wilayah Kerja Puskesmas Baturaden Kabupaten Banyumas - Ekowati, Wahyu; Kamaluddin, Ridlwan; Febrianti, Sandra (Jurusan Keperawatan FIKES UNSOED, 2007)
The issues of nutrition problem are need a seriously attention for pregnant woman. It is not only a pregnant woman that responsible in these issues but also her husband responsibility. In fact, at the community showed that there are perceptions that nutrition problems for pregnant woman are only pregnant woman responsibility, because only women can feel and have experience of pregnancy so all of about pregnancy only for woman responsibility. This perception needs more attention because a pregnancy is the one of a long process for resulting health children and good generation. Nutrition factor is the one of supporting factor contribute to have healthy children .Therefore, the cooperation between the couple for giving attention at nutrition status can realize with real thing. Sharing task and responsibility at home should be emphasized between husband and wife. So nutrition problem for pregnant woman should become collective responsibility. This research described the husband’s role in maintenance pregnant woman nutrition status at Public Health Center Baturaden working area Banyumas district with qualitative design. This research did for 12 weeks with purposive sampling were a couple that had pregnant woman. Collecting data was done with in depth interview and participating observation or unstructured observation. The result of this research showed that there was a low level husband’s role in maintenance pregnant woman nutrition status with predisposition factors were lack of knowledge economic factor and gender equity perception in their family responsibility